Strengthening Education on the Importance of Ethical use of Chatgpt in the Compilation of Student Written Works at Sma Negeri 1 Kedungwuni, Pekalongan Regency - Khumaedi, Muhammad; Bahatmaka, Aldias; Rumondang, Juwita Ria; Bahatmaka, Antama; Fahmi, Fiqri Fadillah; Prasdika, Tegar Oki; Laksono, Aryo; Habibullah, Muhammad; Muclisin, Choirul Anton (Edumedia Solution, 2026)
Learning media in the computer and internet era can help teachers and students learn better. ChatGPT is an AI system that enables conversational interaction through text, can help students understand complex subject matter and improve their learning outcomes. Because the answers are This application is very popular with students because it is well-structured and can solve problems in a short time. However, AI technology, especially Generative Pre-trained Transformer (Chat GPT), has been very important for the advancement of education. In addition, it has an impact on student creativity, originality, and their learning process. This study collected data on student perceptions of the ethics of using ChatGPT. In addition, the written work created was evaluated for its quality. It is hoped that the results of this study will improve our understanding of the possibilities and difficulties of integrating ChatGPT in education. The results of the training on understanding the ethics of using ChatGPT in writing scientific papers for students of SMA Negeri 1 Kedungwuni, Pekalongan Regency, obtained several conclusions: The training was carried out smoothly to students covering the ethical material of using ChatGPT with the quality of creating appropriate prompts and an understanding that AI as a writing aid needs to evaluate the output AI provides. In addition, by holding training, students' abilities in utilizing GPT Chat as a tool in writing papers have increased